Fruiting bodies of selected edible mushrooms as a potential source of lovastatin - Kała, Katarzyna; Kryczyk-Poprawa, Agata; Rzewińska, Aleksandra; Muszyńska, Bożena (European food research & technology, 2020)
Agaricus bisporus , Cantharellus cibarius , Imleria badia , and Lentinula edodes are among the most popular species of edible mushrooms in Poland. These edible mushrooms are an important source of biologically active substances exhibiting beneficial (e.g., antioxidant, antitumor, antimicrobial, anti-inflammatory) effects on the human body. The fruiting bodies of edible mushrooms are also a valuable source of lovastatin, which belongs to a group of compounds, called statins, commonly used as cholesterol-lowering drugs. Due to the presence of lovastatin, edible mushrooms can be useful in the prevention of hypercholesterolemia. Therefore, the aim of this study was to determine the content of lovastatin in the selected species of edible mushrooms and to evaluate its release into artificial digestive juices. This study was the first to determine the release of lovastatin into digestive juices after the extraction of materials obtained from edible mushrooms. The largest amount of lovastatin was found in the fruiting bodies of C. cibarius (67.89 mg/100 g d.w.), and the smallest in those of L. edodes (0.95 mg/100 g d.w.). The amount of lovastatin released from the extracts of the examined species into digestive juices was found to be relatively low. The highest content after incubation in artificial gastric juice was detected for the fruiting bodies of L. edodes (0.02 mg/100 g d.w.) and after incubation in the intestinal juice for the mycelium from the in vitro cultures of L. edodes (0.51 mg/100 g d.w.). Thus, the results of the present study showed that due to its ability to accumulate lovastatin from culture medium, L. edodes mycelium can be used to obtain a product with increased hypolipidemic activity.